Determinant of Output Creative Economic Subsectors: Case Study Culinary MSMEs Blue Beach Tanjung Bumi Bangkalan dan Lon-Malang Beach Sampang - Prasetyo, Alvin Sugeng; Wantara, Pribanus; Umar, Dimas Mahmudi (Buletin Ekonomika Pembangunan, 2024)
The method used in this research is multiple regression, with as many micro and small enterprises as possible, with as many as 152 samples. The estimation results show that capital, labor, raw materials for production, and electrical energy have a significant effect on production sold by traders. Still, the use of technology has not had a significant effect on production sold by traders. The Research results found that culinary MSMEs in the Blue Beach and Lon Malang tourist destination have not yet optimized digitalization. For example, they lack mastery of technology and have not used e-payment, so they have not been able to increase revenue. Keywords: Blue Beach, Lon Malang, multiple regression,